Feasibility Study of Public Health Center X - Tambunan, Willy; Pawitra, Theresia Amelia; Siagian, Riko Yehezkiel (TALENTA Publisher, 2021)
Public Health Center X is the first level health facility service provider in subdistrict X. Established in 1975, UPT Puskesmas X has never conducted a feasibility study which has been regulated since 2014. Based on these problems, this study aims to conduct a feasibility study on a new building. Aspects contained in Permenkes No. 75 of 2014 namely aspects of location, buildings, facilities and infrastructure, health equipment, personnel, and organization. There is a health center design stage which is made in accordance with the criteria of the Minister of Health No. 75 of 2014. Based on the results of research conducted on the new building of Public Health Center X, it is known that the location aspect meets 87.5% of the location criteria, the building aspect meets 100% of the building suitability, the facilities and infrastructure aspect meets 100% of the eligibility criteria, the equipment aspect only meets 34% of the equipment that must be owned, the manpower aspect fulfills 73% of the total workforce owned, and the organizational aspect meets 100% of the conformity of the organizational structure, so that overall Public Health Center X has a feasibility percentage of 82.4%. Public Health Center X needs to evaluate and improve. Improvements were made to the location aspect, namely, parking facilities by increasing the capacity of the parking lot. Then do the procurement and purchase of medical equipment because there are still 66% of equipment that is lacking, as well as adding health workers to the positions of public health workers, environmental health workers, and workers.